Students’ Perceptions of the Implementation of the Teacher Training and Development Program (TTDP) in Improving Teaching Skills - Nurul Azizah; Halida Umami; Zuhrotul Mufidah; Ilham Mulyadi (Didaktika: Jurnal Kependidikan, 2025)
The growing gap between the curriculum taught in educational institutions and the demands of the workforce in the education sector highlights the need for more relevant teacher training, emphasizing the importance of evaluating microteaching programs. Therefore, the Faculty of Tarbiyah at UNIDA Gontor developed a microteaching program named the Teacher Training and Development Program (TTDP). The purpose of this study is to explore students' perceptions of the implementation of the Teacher Training and Development Program (TTDP) at the Faculty of Tarbiyah, UNIDA Gontor. This study investigates the effectiveness of the TTDP as perceived by 6th-semester students. The study uses a quantitative design with a survey approach. Data was collected through a Likert scale questionnaire distributed via Google Forms. The collected data was analyzed descriptively with percentages, and through qualitative analysis, including data collection, reduction, presentation, and drawing conclusions. The study assesses students' perceptions of various teaching skills. The results show: 1) Based on students' perceptions, there is a strong positive impact of the TTDP program in developing teaching skills, with the majority of students reporting significant improvement in their ability to explain material, manage classrooms, ask meaningful questions, guide discussions, apply diverse teaching methods, and provide effective reinforcement. 2) This study found the innovative design of the TTDP program, which differs from other microteaching programs by integrating the needs of various types of educational institutions (madrasah, schools, and pesantren) in the teaching materials. 3) This study highlights the contribution of TTDP in addressing curriculum gaps and aligning teacher education with market needs, so the TTDP teacher training model can be implemented in various education faculties across Indonesia.